Integrin-specific hydrogels as adaptable tumor organoids for malignant B and T cells. (December 2015) - Tian, Ye F.; Ahn, Haelee; Schneider, Rebecca S.; Yang, Shao Ning; Roman-Gonzalez, Lidia; Melnick, Ari M.; Cerchietti, Leandro; Singh, Ankur
Abstract: Non-Hodgkin lymphomas are a heterogeneous group of lymphoproliferative disorders of B and T cell origin that are treated with chemotherapy drugs with variable success rate that has virtually not changed over decades. Although new classes of chemotherapy-free epigenetic and metabolic drugs have emerged, durable responses to these conventional and new therapies are achieved in a fraction of cancer patients, with many individuals experiencing resistance to the drugs. The paucity in our understanding of what regulates the drug resistance phenotype and establishing a predictive indicator is, in great part, due to the lack of adequate ex vivo lymphoma models to accurately study the effect of microenvironmental cues in which malignant B and T cell lymphoma cells arise and reside. Unlike many other tumors, lymphomas have been neglected from biomaterials-based microenvironment engineering standpoint. In this study, we demonstrate that B and T cell lymphomas have different pro-survival integrin signaling requirements (αvβ3 and α4β1) and the presence of supporting follicular dendritic cells are critical for enhanced proliferation in three-dimensional (3D) microenvironments. We engineered adaptable 3D tumor organoids presenting adhesive peptides with distinct integrin specificities to B and T cell lymphoma cells that resulted in enhanced proliferation, clustering, and drug resistance to the chemotherapeutics and a new class of histone deacetylase inhibitor (HDACi), Panobinostat. In Diffuse Large B cell Lymphomas, the 3D microenvironment upregulated the expression level of B cell receptor (BCR), which supported the survival of B cell lymphomas through a tyrosine kinase Syk in the upstream BCR pathway. Our integrin specific ligand functionalized 3D organoids mimic a lymphoid neoplasm-like heterogeneous microenvironment that could, in the long term, change the understanding of the initiation and progression of hematological tumors, allow primary biospecimen analysis, provide prognostic values, and importantly, allow a faster and more rational screening and translation of therapeutic regimens.